Foot Pronation Contributes to Altered Lower Extremity Loading After Long Distance Running - Mei, Qichang; Gu, Yaodong; Xiang, Liangliang; Baker, Julien S.; Fernandez, Justin (Frontiers in Physiology, 2019)
This study aimed to investigate the changes of foot postures, joint kinematics, moments and contact forces to the lower extremity after a 5k treadmill run, and analyze correlation of foot posture index with knee and ankle loading. Twenty recreational male heel strike runners participated in this study. All had history of running and free from lower extremity injuries or foot deformities. Foot posture, three-dimensional markers trajectories, ground reaction force and surface electromyography (EMG) were recorded pre and post 5k treadmill running with standard running shoes. Musculoskeletal modelling techniques from OpenSim were employed to calculate the joint kinematics, moments and contact forces. Simulated EMG activations were compared against experimental EMG signals to validate the model. One-dimensional statistical parametric mapping (SMP1d) package was used for statistical analysis. Hip moments and contact forces to joint increased significantly and temporally during initial contact and mid stance post 5k. Knee abduction moment and sup-inf contact force increased but extension moment decreased significantly and temporally. The significantly increased ankle plantarflexion moment and contact forces were observed temporally during stance. Foot posture index showed increased correlations with peak knee and ankle moments. Recreational male runners presented pronated foot postures after 5k treadmill running with neutral shoes. Changes of lower extremity angles, moments and contact forces during stance could integrate into etiological framework of loads magnitude and distribution to investigate the causation of running-related injuries.